Prevalence and Trends of Overweight and Obesity Among Children and Adolescents in Turkey: AMeta-analysis - Yavuz, Cansev Meşe (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Over the past 40 years, the prevalence of overweight and obesity in children and adolescents has increased significantly worldwide, especially in low and middleincome countries. Studies have reported an increase in these rates also Turkey. Objective: to determine the prevalence of overweight and obesity based on articles published from 2000 to 2020 and conducted with children and adolescents ages 5-19. Besides, it was aimed to reveal the trend of overweight and obesity prevalence over the years. Methods: For this purpose, publications between 2000 and 2020 were searched in Pubmed, Web of Science and Ulakbim databases. Publications were reviewed considering the selection criteria and a total of 69 articles were included in the study. The heterogeneity of the studies was tested and funnel plot, Begg’s test, Egger’s test, Duval and Tweedie’s trim and fill methods were used to determine publication bias. Results: The pooled prevalence of overweight was 13.3% (95% Cl: 12.3-14.4), obesity was 7.8% (95% CI: 6.8-8.8). It was found that overweight and obesity prevalences increased between 2000-2004 and 2010-2019 periods. Conclusion: More effective strategies and policies should be implemented to substantially reduce or prevent childhood overweight and obesity. International Journal of Human and Health Sciences Vol. 07 No. 01 Jan’22 Page: 20-30